Copyright Policy and the Problem of Generalizing - Subotnik, Eva E. (The Columbia Journal of Law & the Arts, 2015)
Today we have heard a variety of concerns expressed by professional authors, artists and performers. But one of the toughest aspects of determining how to make the copyright system work better is generalizing about what is and is not working. In these brief remarks, I would like to identify three areas that demonstrate this difficulty. At the outset, a disclaimer: I took the animating theme of this Symposium to be the improvement of the financial stake of individual authors in some kind of direct way. This mode of analysis should be distinguished from other approaches, equally valid, that would seek out ways of benefitting individual creators by improving the financial position of Hollywood studios, record labels, publishers and the like. With that assumption stated, here are the three contexts that reflect the difficulty in generalizing: (1) the issue of identifying the kinds of creative activity that should properly be the focus of the copyright system; (2) the issue of evaluating copyright law’s application to the Internet, which is both a catalyst for and detractor from profitable authorship; and (3) the issue of framing the costs of enforcing copyright interests.